Diverse seed banks favour adaptation of microalgal populations to future climate conditions. (10th December 2015) - Kremp, Anke; Oja, Johanna; LeTortorec, Anniina H.; Hakanen, Päivi; Tahvanainen, Pia; Tuimala, Jarno; Suikkanen, Sanna
Summary: Selection of suitable genotypes from diverse seed banks may help phytoplankton populations to cope with environmental changes. This study examines whether the high genotypic diversity found in the Baltic cyst pool of the toxic dinoflagellate A lexandrium ostenfeldii is coupled to phenotypic variability that could aid short‐term adaptation. Growth rates, cellular toxicities and bioluminescence of 34 genetically different clones isolated from cyst beds of four Baltic bloom sites were determined in batch culture experiments along temperature and salinity gradients covering present and future conditions in the Baltic Sea. For all parameters a significant effect of genotype on the response to temperature and salinity changes was identified. General or site‐specific effects of the two factors remained minor. Clones thriving at future conditions were different from the best performing at present conditions, suggesting that genotypic shifts may be expected in the future. Increased proportions of highly potent saxitoxin were observed as a plastic response to temperature increase, indicating a potential for higher toxicity of future blooms. The observed standing variation in Baltic seed banks of A . ostenfeldii suggests that the population is likely to persist under environmental change.